Metformin Suppresses the Progress of Diabetes-Accelerated Atherosclerosis by Inhibition of Vascular Smooth Muscle Cell Migration Through AMPK–Pdlim5 Pathway - Yan, Yi; Li, Ting; Li, Zhonghao; He, Mingyuan; Wang, Dejiang; Xu, Yingyi; Yang, Xuewen; Bai, Yuanyuan; Lao, Yi; Zhang, Zhiyong; Wu, Wei (Frontiers in Cardiovascular Medicine, 2021)
Backgrounds: Our previous work revealed that AMP activated protein kinase (AMPK) activation inhibit vascular smooth muscle cells migration in vitro by phosphorylating PDZ and LIM domain 5 (Pdlim5). As metformin is an AMPK activator, we used a mouse vascular smooth muscle cell (VSMC) line and a Myh11-cre-EGFP mice to investigate whether metformin could inhibit migration of VSMCs in vitro and in a wire-injury model in vivo. It is recognized that VSMCs contribute to the major composition of atherosclerotic plaques. In order to investigate whether AMPK-Pdlim5 pathway is involved in the protective function of metformin against atherosclerosis, we utilized ApoE−/− male mice to investigate whether metformin could suppress diabetes-accelerated atherosclerosis by inhibition of VSMCs migration via AMPK-Pdlim5 pathway. Methods: Mouse VSMCs cell line was exogenously transfected wildtype, phosphomimetic or unphosphorylatable Pdlim5 mutant before metformin exposure. Myh11-cre-EGFP mice were treated with saline solution or metformin after subjected to wire injury in carotid artery to study whether metformin could inhibit migration of medial VSMCs into neo-intima. In order to investigate whether AMPK-Pdlim5 pathway is involved in the protective function of Metformin against atherosclerosis, ApoE−/− male mice were divided randomly into control, streptozocin and high fat diet-induced diabetes mellitus, STZ+HFD together with metformin or Pdlim5 mutant carried adenovirus treatment groups. Results: It was found that metformin could induce phosphorylation of Pdlim5 and inhibition of cell migration as a result. Exogenous expression of phosphomimetic S177D-Pdlim5 inhibits lamellipodia formation and migration in VSMCs. It was also demonstrated that VSMCs contribute to the major composition of injury-induced neointimal lesions, while metformin could alleviate the occlusion of carotid artery. The data of ApoE−/− mice showed increased plasma lipids and aggravated vascular smooth muscle cells infiltration into the atherosclerotic lesion in diabetic mice were observed Metformin alleviated diabetes-induced metabolic disorders and atherosclerosis, also reduced VSMCs infiltration in atherosclerotic plaques, while Pdlim5 phospho-abolished mutant carried adenovirus S177A-Pdlim5 undermine the protective function of metformin. Conclusions: The activation of AMPK-Pdlim5 pathway by metformin could interrupt the migratory machine of VSMCs and inhibit cell migration in vitro and vivo. The maintenance of AMPK activity by metformin is beneficial for suppressing diabetes-accelerated atherosclerosis.